The Influence of Green Accounting on Financial Performance through Corporate Sustainability Management System (Study on the Food and Beverage Sector on the Indonesia Stock Exchange 2020-2022) - Iqbal, Muhammad (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2026)
Purpose – This study aims to analyse the effect of implementing environmental sustainability practices on the company's financial performance. Methods – This research uses quantitative methods. The samples used in this study are food and beverage companies listed on the IDX in 2020 - 2022, publish financial reports and have the data needed for variable measurement. The dependent variable in this study is financial performance. Green accounting independent, Corporate Sustainability Management System intervening variable Findings - The results show that green accounting and system affect financial performance, green accounting no affects Corporate Sustainability Management System. Green Accounting has no effect on financial performance through CSMS. Implications - Theoretically, this study enriches stakeholder and legitimacy theories by showing that Green Accounting and Corporate Sustainability Management Systems can improve financial performance, although CSMS does not mediate the relationship between Green Accounting and financial performance. Practically, the findings encourage companies to strengthen sustainability practices, environmental cost management, and sustainability reporting to improve profitability, investor confidence, and long-term competitiveness. Originality - The originality of this study lies in examining CSMS as an intervening variable in the Indonesian food and beverage sector during 2020–2022 and providing new evidence that CSMS does not mediate the influence of Green Accounting on financial performance.